1984
DOI: 10.1530/jrf.0.0710279
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of long-term monolayer cultures of human granulosa cells from follicles of different size and exposed in vivo to clomiphene citrate and hCG

Abstract: To determine the effects of prolonged hCG treatment in vitro upon granulosa cells from follicles of various sizes previously exposed to clomiphene citrate and hCG in vivo, progesterone and relaxin concentrations of spent media were correlated with light microscopic and ultrastructural characteristics. Intact, freshly dispersed cells were characterized by numerous lipid droplets, elliptical mitochondria with tubular or lamellar cristae, moderate rough-surfaced endoplasmic reticulum (RER), sparse smooth-surfaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…5,7,and 8). The presence of a rich network of SER tubules and of a well-developed Golgi apparatus in the GCs confirm that luteinization is in progress (Amsterdam and Rotmensch, 1987;Bjersing, 1967;Schmidt et al, 1984;Suzuki et al, 1981). In this regard, isolated RER cisternae and ribosomes in luteinizing GCs may contribute to luteinization by synthesizing the enzymatic pattern involved in the steroid production (Crisp et al, 1970).…”
Section: Nuclear and Cytoplasmic Organizationmentioning
confidence: 69%
See 3 more Smart Citations
“…5,7,and 8). The presence of a rich network of SER tubules and of a well-developed Golgi apparatus in the GCs confirm that luteinization is in progress (Amsterdam and Rotmensch, 1987;Bjersing, 1967;Schmidt et al, 1984;Suzuki et al, 1981). In this regard, isolated RER cisternae and ribosomes in luteinizing GCs may contribute to luteinization by synthesizing the enzymatic pattern involved in the steroid production (Crisp et al, 1970).…”
Section: Nuclear and Cytoplasmic Organizationmentioning
confidence: 69%
“…Although the loss of architectural and microtopographic integrity due to plating conditions can have marked effects on the structure and metabolism of cultured GCs (Zoller, 1991), fine structural changes superimposable to those described for GCs within the follicle occur spontaneously in vitro, after 12 h of culture in humans (Suzuki et al, 1981) or after 48-72 h in other mammals (Balboni and Zecchi, 1981;Zoller, 1991). These changes are further enhanced when LH/hCG, cyclic adenosine 3 0 5 0 -monophosphate (Soto et al, 1986), hCG-low density lipoproteins (Richardson et al, 1992), clomiphene citrate (Schmidt et al, 1984), or follicular fluid from large follicles (Zoller, 1991) are administered or if GCs are plated onto collagen- (Ben-Rafael et al, 1988) or matrigel-coated dishes (Hwang et al, 2000).…”
Section: Morphodynamics Of Human Gcsmentioning
confidence: 95%
See 2 more Smart Citations
“…Lipid droplets in the CL or cultured luteal cells have been identified by using electron microscopy for several species including humans, rats, rabbits, cows and sheep (Blanchette, 1966;Enders, 1973;Schmidt et al, 1984;O'Shea et al, 1986O'Shea et al, , 1989Yuh et al, 1986;Fields et al, 1992;Fields and Fields, 1996;Towns et al, 1999). In our study, we not only identified presence and localization of LDs in LLC and SLC but we also quantified LDs demonstrating that the mean and median volume of individual LD was greater in SLC than LLC.…”
Section: Discussionmentioning
confidence: 99%